2017
DOI: 10.17129/botsci.780
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ecology of the threatened "star cactus" <em>Astrophytum ornatum</em> (Cactaceae): a strategy of continuous reproduction with low success

Abstract: Controlled pollinations to determine the mating system and determination of the Outcrossing Index (OCI), the pollen /ovule ratio and breeding system. Results: Astrophytum ornatum produced flower buds throughout the year, but 89.2% of them were aborted. Four events of ephemeral flowering population were presented per year. The species is self-incompatible and controlled pollinations indicated pollinator limitation of several bee species. The OCI indicates that the species is facultative xenogamous, and pollen/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 38 publications
(62 reference statements)
1
7
0
13
Order By: Relevance
“…Para N. conoidea, los pulsos observados parecen ser producto en su mayor parte de pulsaciones a nivel de individuos, ya que entre el 81 y 73 % de estos produjeron flores en más de un pulso por año. Este patrón no ha sido reportado en ninguna cactácea globosa, ya que generalmente los estudios de fenología floral se han abocado a determinar la duración del periodo de floración y los picos observados a través de censos mensuales o quincenales sin un seguimiento individual de las flores (McIntosh 2002, Nassar & Ramírez 2004, Matias-Palafox et al 2017. Solamente encontramos en la literatura un trabajo donde se evidencia la ocurrencia de pulsos en la cactácea columnar Pilosocereus leucocephalus (Munguía-Rosas & Sousa 2010).…”
Section: Añounclassified
“…Para N. conoidea, los pulsos observados parecen ser producto en su mayor parte de pulsaciones a nivel de individuos, ya que entre el 81 y 73 % de estos produjeron flores en más de un pulso por año. Este patrón no ha sido reportado en ninguna cactácea globosa, ya que generalmente los estudios de fenología floral se han abocado a determinar la duración del periodo de floración y los picos observados a través de censos mensuales o quincenales sin un seguimiento individual de las flores (McIntosh 2002, Nassar & Ramírez 2004, Matias-Palafox et al 2017. Solamente encontramos en la literatura un trabajo donde se evidencia la ocurrencia de pulsos en la cactácea columnar Pilosocereus leucocephalus (Munguía-Rosas & Sousa 2010).…”
Section: Añounclassified
“…This has led to an increased interest in studying various aspects of their biology, including their reproductive biology (Mandujano et al 2010;Díaz-Segura et al 2017;Jiménez-Sierra et al 2019;among others). and some studies have considered sympatric Cactaceae (McIntosh 2002;Giorgis et al 2015;Eggli & Giorgetta 2017;Matías-Palafox et al 2017;Ferreira et al 2018;Guerrero et al 2019). The study of the reproductive biology of sympatric Cactaceae may shed light on the interference or facilitation of maintaining shared pollinators, which helps to understand the ecosystem services of pollination within xerophyte communities as well as provide arguments for the conservation of these ecosystems (Eggli & Giorgetta 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed marked abiotic differences between forest edges and interiors (Riutta et al 2014;Wicklein et al 2012) that can affect the reproductive patterns of plant communities and their associated species (Athayde & Morellato 2014). Phenological studies in anthropogenic landscapes, however, have largely been limited to population studies (e.g., Vogado et al 2016;Matias-Palafox et al 2017;Oliveira et al 2019), whereas the few studies with a community approach have showed increased phenological intensities of trees at forest edges (Fortunato & Quirino 2016), with synchronize different from those in the forest interior (Cunningham 2000;Reznik et al 2012). Phenological changes at the species level in response to habitat modifications can vary among functional groups and successional stages (Xiao et al 2016).…”
Section: Introductionmentioning
confidence: 99%